Description of a new deep-water species of Heteroclinus (Pisces: Teleostei: Clinidae), from southern Australia - Hoese, Douglass F.; Pogonoski, John J. (Zootaxa, 2021)
Heteroclinus argyrospilos, n. sp. is described as a new species from specimens sampled by sled and dredge in 55–100 m off South Australia and Western Australia. The species has a strongly compressed body and spatulate orbital tentacle similar to some shallow water species, particularly those of the Heteroclinus heptaeolus complex, which is characterized by having three segmented dorsal-fin rays, with the last two rays widely separate from the first ray. It is distinct from other Australian clinids in having two segmented dorsal-fin rays, well separated from the last dorsal-fin spine and a reduced lateral line on the body. It is known from a greater depth than other members of the genus.